ANALYSIS OF STUDENT SERVICE QUALITY WITH SERVQUAL METHOD, QFD, AND CONTINUOUS IMPROVEMENT - Susanto, Andri; Nursanti, Ellysa; Vitasari, Prima (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
Sekolah Tinggi Teknik (STT) Malang is one of College in Malang City. Service quality problems that students complain about include academic services, wi-fi facilities, and facility issues. This study aims to determine the current student service mapping with the SERVQUAL method, applicative suggestions based on the QFD method, and service improvements based on continuous improvement methods. The research was conducted by distributing questionnaires randomly to 250 students. The results showed that the attributes of adequate motorcycle parking space, wifi/internet facilities, the ease of students submitting academic complaints, and the ease of submitting complaints on facilities were the main priorities for improvement. The main priority for improvement is educational services, such as providing face-to-face facilities and online media for submitting academic complaints.